Physicochemical quality of cow’s milk mozzarella cheese using rennet enzyme and lime juice as a natural coagulant - Rizal, Choirul Syamsul; Windyasmara, Ludfia (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2025)
Cow’s milk is a natural food source rich in essential nutrients and can be processed into various value-added products, including mozzarella cheese. Although traditional mozzarella is made from buffalo milk, cow’s milk is now more commonly used due to its wider availability and lower production costs. This study evaluated the effect of lime (Citrus aurantiifolia) juice as a natural coagulant on the sensory, physical, and chemical characteristics of cow’s milk mozzarella. A Completely Randomized Design (CRD) was applied using 500 mL of cow’s milk, 15 g coarse salt, and 0.5 mL rennet enzyme per batch, with varying volumes of lime juice. Data were analyzed by ANOVA, followed by Duncan’s Multiple Range Test (DMRT) at P < 0.05. The resulting mozzarella showed soluble protein of 0.65–1.12%, moisture of 45.67–49.33%, yield of 8.80–11.00%, texture (penetrometer) of 0.05–1.58 mm/g, and meltability of 32.04–43.82%. Lime juice level significantly affected yield, texture, and meltability, but not soluble protein or moisture.